2010
DOI: 10.1016/j.bpj.2010.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Tradeoff of Higher Activity in MMP-12 for Enhanced Stability and Flexibility in MMP-3

Abstract: The greater activity of MMP-12 than MMP-3 toward substrates from protein fibrils has been quantified. Why is MMP-12 the more active protease? We looked for behaviors associated with the higher activity of MMP-12 than MMP-3, using nuclear magnetic resonance to monitor backbone dynamics and residue-specific stabilities of their catalytic domain. The proteolytic activities are likely to play important roles in inflammatory diseases of arteries, lungs, joints, and intestines. Nuclear magnetic resonance line broade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…Use of E219A-inactivated MMP-12 prevented digestion of Eln-20. The extent of this structural perturbation is localized to residue 219 in the active site (49,(71)(72).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of E219A-inactivated MMP-12 prevented digestion of Eln-20. The extent of this structural perturbation is localized to residue 219 in the active site (49,(71)(72).…”
Section: Resultsmentioning
confidence: 99%
“…5, a and c) to account for the high elastase activity of MMP-12 is that its advantage over MMP-3 is not in K m , but rather 13.5-fold in k cat ( Table 1). The lower k cat of MMP-3 could be related to its greater extent of millisecond motions surrounding the active site (72).…”
Section: Of Ref 33)mentioning
confidence: 99%
“…We set out to discover whether the well-characterized MMP-12 22, 23, 24, 25, 26 binds directly to lipid bilayers and plasma membranes of living cells. Our results take on unexpected relevance to the recent question of how active MMPs enter and move through cells 2, 27, 28 .…”
mentioning
confidence: 99%
“…9A). 15 N relaxation experiments have shown them to be flexible (59). Intriguingly, R 1 measurements (60) showed that both these areas, which together form the upper and lower rims of the narrowest part of the active site (Fig.…”
Section: Resultsmentioning
confidence: 99%